1981
DOI: 10.1007/bf00271189
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of a cloned cDNA copy of TMV (cowpea strain) RNA, including the assembly origin, the coat protein cistron, and the 3′ non-coding region

Abstract: The cloned cDNA derived from the 3' end of cowpea strain (Cc) RNA of tobacco mosaic virus (TMV) has been sequenced. Substantial sequence information of 1,060 nucleotides from the 3' end of the RNA reveals some interesting features: (1) the coat protein cistron corresponds to residues 210-701 from the 3' end. Some errors in the amino acid sequence previously reported have been corrected and the revised total length of the coat protein is 162 amino acid residues. The capping site of the coat protein mRNA is at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…A consensus for the tymoviral tRNA-like structure was made and compared to those of both prokaryotic and eukaryotic tRNAva' (Van Belkum et al, 1987a). The cowpea strain of tobacco mosaic virus (CcTMV or sunhemp mosaic virus) was also included, because its 3'-terminal structure resembles that of TYMV RNA rather than that of the tobainoviral RNAs (Meshi et al, 1981 ;Rietveld et al, 1984). We adapt here these consensus structures, using the latest compilation of tRNA sequences and latest nucleotide sequences of tymoviral RNAs (Sprinzl et al, 1989;Ding et al, 1990a and references therein;Ding et al, 1990b;Fig.…”
Section: Tvmo Virusesmentioning
confidence: 99%
“…A consensus for the tymoviral tRNA-like structure was made and compared to those of both prokaryotic and eukaryotic tRNAva' (Van Belkum et al, 1987a). The cowpea strain of tobacco mosaic virus (CcTMV or sunhemp mosaic virus) was also included, because its 3'-terminal structure resembles that of TYMV RNA rather than that of the tobainoviral RNAs (Meshi et al, 1981 ;Rietveld et al, 1984). We adapt here these consensus structures, using the latest compilation of tRNA sequences and latest nucleotide sequences of tymoviral RNAs (Sprinzl et al, 1989;Ding et al, 1990a and references therein;Ding et al, 1990b;Fig.…”
Section: Tvmo Virusesmentioning
confidence: 99%
“…The first one, in the amino part of the protein, has homology with the nsP1 protein of alphaviruses and with the amino part of other proteins implicated in the Ohno et al (1984), Goelet et at. (1982), Meshi et at. (1981Meshi et at.…”
Section: Organization Of the 126k/183k Gene Sequencementioning
confidence: 99%
“…Complete sequences of the TMV, TYMV, A1MV and BMV coat protein messengers (Guilley et al, 1979;Ahlquist et al, 1981b;Meshi et aL, 1981), although milestones in their own right, have revealed little other than the length of leader, confirmation of coat protein sequences, assignment of coding triplets used, and the hypothetical secondary structure. Sequence data are now needed for complete genomes; this then needs to be extended to different isolates of the same virus with differences in symptomatology and host range, and to viruses of the same group with different structural, and biological phenomena.…”
Section: Complete and Comparative Sequencesmentioning
confidence: 99%
“…(iii) The whole virus RNA may be translated as a monocistronic messenger and the resultant polyprotein is then processed into smaller products. A fourth possible mechanism of translating virus RNA in more than one reading frame has not yet been demonstrated in plant viruses, although the possibility has been suggested for CcTMV (Meshi et al, 1981) and for southern bean mosaic virus (SBMV; Ghosh et al, 1981).…”
Section: Genome Strategiesmentioning
confidence: 99%